CORE Learning Model Assisted by Mind Mapping to Improve Elementary School Students' Javanese Skills - Maruti, Endang Sri (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
The importance of this research is due to the challenges encountered in learning Javanese in elementary schools, particularly regarding the material of Javanese script writing. The gap in the literature or the difference between theory and practice is that previous studies have widely explored the application of the CORE learning model across various subject areas, such as science and mathematics. Nonetheless, there exists a limited number of studies that combine the CORE learning model with mind-mapping techniques, specifically within the context of Javanese language instruction at the elementary level. The purpose of this study is to describe the application of the CORE learning model assisted by mind mapping in improving Javanese language learning outcomes. The research method employed is classroom action research. Data collection methods were through observation, tests, and interviews. The data analysis process used in the research was interactive analysis. The main findings revealed that the mind mapping-assisted CORE learning model could improve the learning outcomes of the Javanese language of 5th-grade elementary school students. In its implementation, students who were taught using the CORE learning model assisted by mind mapping exhibited a significant increase in their Javanese language learning outcomes. The conclusion is that the mind mapping-assisted CORE learning model is applicable in elementary school Javanese language learning. The implications of these results can be used by educators as a basis for implementing futuristic models and adaptive media combinations in language learning with several similar problems.